Health status of free-ranging ring-necked pheasant chicks (Phasianus colchicus) in North-Western Germany - Liebing, J. (PLoS One, 2020)
Being a typical ground-breeding bird of the agricultural landscape in Germany, the pheasant has experienced a strong and persistent population decline with a hitherto unexplained cause. Contributing factors to the ongoing negative trend, such as the effects of pesticides, diseases, predation, increase in traffic and reduced fallow periods, are currently being controversially discussed. In the present study, 62 free-ranging pheasant chicks were caught within a two-year period in three federal states of Germany; Lower Saxony, North Rhine-Westphalia and Schleswig-Holstein. The pheasant chicks were divided into three age groups to detect differences in their development and physical constitution. In addition, pathomorphological, parasitological, virological, bacteriological and toxicological investigations were performed. The younger chicks were emaciated, while the older chicks were of moderate to good nutritional status. However, the latter age group was limited to a maximum of three chicks per hen, while the youngest age class comprised up to ten chicks. The majority of chicks suffered from dermatitis of the periocular and caudal region of the head (57–94%) of unknown origin. In addition, intestinal enteritis (100%), pneumonia (26%), hepatitis (24%), perineuritis (6%), tracheitis (24%), muscle degeneration (1%) and myositis (1%) were found. In 78% of the cases, various Mycoplasma spp. were isolated. Mycoplasma gallisepticum (MG) was not detected using an MG-specific PCR. Parasitic infections included Philopteridae (55%), Coccidia (48%), Heterakis/Ascaridia spp. (8%) and Syngamus trachea (13%). A total of 8% of the chicks were Avian metapneumovirus (AMPV) positive using RT-PCR, 16% positive for infectious bronchitis virus (IBV) using RT-PCR, and 2% positive for haemorrhagic enteritis virus (HEV) using PCR. All samples tested for avian encephalomyelitis virus (AEV), infectious bursal disease virus (IBDV) or infectious laryngotracheitis virus (ILTV) were negative. The pool samples of the ten chicks were negative for all acid, alkaline-free and derivative substances, while two out of three samples tested were positive for the herbicide glyphosate. Pheasant chick deaths may often have been triggered by poor nutritional status, probably in association with inflammatory changes in various tissues and organs as well as bacterial and parasitic pathogens. Theses impacts may have played a major role in the decline in pheasant populations.